The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1475-2875-13-471
|View full text |Cite
|
Sign up to set email alerts
|

Metal-chloroquine derivatives as possible anti-malarial drugs: evaluation of anti-malarial activity and mode of action

Abstract: BackgroundMalaria still has significant impacts on the world; particularly in Africa, South America and Asia where spread over several millions of people and is one of the major causes of death. When chloroquine diphosphate (CQDP) lost its efficiency as a first-line anti-malarial drug, this was a major setback in the effective control of malaria. Currently, malaria is treated with a combination of two or more drugs with different modes of action to provide an adequate cure rate and delay the development of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…An improvement in the potency against intraerythrocytic stages of P. falciparum was observed in most cases, in comparison with metalfree CQ. An interesting finding is that the antiparasitic potency is not superior to complexes containing two CQ molecules in the structure, which indicates that metal complexes are not mere drug delivery systems that act by releasing CQ and that, instead, the entire chemical structure is involved in the antiparasitic activity (Sánchez-Delgado et al 1996;Goldberg et al 1997;Lewis et al 1997;Navarro et al 1997Navarro et al , 2004Navarro et al , 2011aNavarro et al , b, 2014Rajapakse et al 2009). Given this promising outlook, CQ analogs have been employed in the metal complex composition in the last years and given rise to many successful outcomes (Dubar et al 2011(Dubar et al , 2013Glans et al 2012a, b;Salas et al 2013;Ekengard et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in the potency against intraerythrocytic stages of P. falciparum was observed in most cases, in comparison with metalfree CQ. An interesting finding is that the antiparasitic potency is not superior to complexes containing two CQ molecules in the structure, which indicates that metal complexes are not mere drug delivery systems that act by releasing CQ and that, instead, the entire chemical structure is involved in the antiparasitic activity (Sánchez-Delgado et al 1996;Goldberg et al 1997;Lewis et al 1997;Navarro et al 1997Navarro et al , 2004Navarro et al , 2011aNavarro et al , b, 2014Rajapakse et al 2009). Given this promising outlook, CQ analogs have been employed in the metal complex composition in the last years and given rise to many successful outcomes (Dubar et al 2011(Dubar et al , 2013Glans et al 2012a, b;Salas et al 2013;Ekengard et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, identifying new drug targets with new mechanisms of action of the drug may help in fighting the disease [4] [8]. Today, many other natural products and synthetic anti-malaria agents have been designed to target different enzymes involved in parasitic life cycle [6] [10]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…PtCQ-Loaded Liposomes Prepared Using the Thin Drug-Lipid Film Method Navarro et al mentioned the high lipophilicity of metal chloroquine complexes 28) and Khokhar et al demonstrated the preparation of highly stable lipophilic cisplatin complex/liposomes with high encapsulation ratios. 29) Consequently, in this study we succeeded in loading the PtCQ complex into neutral and cationic liposomes at reasonable drug-to-lipid ratios by incorporating the drug into the lipid phase using the thin drug-lipid film method.…”
Section: Resultsmentioning
confidence: 99%